Influential Article Review - Leadership Traits and Its Potential Impact on CSR Perception (Journal of Leadership, Accountability and Ethics, 2019)
This paper examines corporate social responsibility. We present insights from a highly influential paper. Here are the highlights from this paper: The dark triad is a psychological term explaining individual negative dispositions. It is composed of Machiavellianism, which is a tendency to manipulate others to gain advantage, psychopathy, which is a general lack of empathy, and narcissism, which is excessive self-love. The negative effects of any leader’s unethical behaviors on society necessitate an examination of the relationship between the leader’s undesirable propensity and the corporate social responsibility (CSR). The literature reveals that the characteristics and traits of an organization’s leader affect the ethics of the organization and that the leader’s ethical perception and judgment can affect CSR. Accordingly, it is critical for a leader with the dark triad trait to check his or her perception of CSR. In addition, it is necessary to determine how the individual performance-based compensation system moderates the relationship between a leader’s dark triad trait and CSR perception. Although a compensation system is useful in enhancing performance, it can have negative effects due to excessive and exclusive emphasis on performance. Empirical results have shown that Machiavellianism and psychopathy negatively affect the perception of CSR as a prima facie duty. Especially in this relation, the individual performance-based compensation system improves the negative relationship between Machiavellianism and CSR perception, and exacerbates the negative relationship between psychopathy and CSR perception. However, the psychopathy trait has only a negative relationship with the perception of CSR as a top priority, and the other traits have no significant relationship with the perception of CSR as a top priority. The study conclusions are summarized as follows: 1) the leader’s perception of CSR is affected by his or her negative traits like Machiavellianism and psychopathy, 2) an organization needs to investigate the performance evaluation system and indicators for avoiding a negative influence of the system, and 3) it is necessary to find effective and practical managerial approaches capable of controlling the potential negative traits desirably. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.
Keywords: Compensation system; CSR; Dark triad; Machiavellianism; Narcissism; Psychopathy